Political Communication in Medan Regional Head Election during the Covid-19 Pandemic - Arifin Saleh; Rudianto Rudianto; Akhyar Anshori; Abrar Adhani (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
The implementation of the 2020 Regional Head Elections (Pilkada) in the Covid-19 pandemic requires cooperation and synergy of every existing element to uphold the constitution and suppress the outbreak of Covid-19. This study was conducted to determine the public’s perception of whether the simultaneous regional elections in 2020 became a new cluster in the spread of covid-19. The method used in this study is a descriptive quantitative approach, using a questionnaire as a data collection tool. The data obtained were analyzed through percentage analysis and multiple regression tests. This study found that 400 respondents (36.36%) did not trust the information conveyed by mass media and social media regarding the development of Covid-19. Meanwhile, 553 respondents (50.30%) stated that they would attend the polling stations only if there were strict safety procedures and implementation of health protocols.